Inflammatory Activities in Type 2 Diabetes Patients With Co-morbid Angiopathies and Exploring Beneficial Interventions: A Systematic Review - Nwadiugwu, Martin C. (Frontiers in Public Health, 2021)
Background Diabetes is a long-term condition that can be treated and controlled but do not yet have a cure; it could be induced by inflammation and the goal of managing it is to prevent additional co-morbidities and reduce glycemic fluctuations. There is a need to examine inflammatory activities in diabetes-related angiopathies and explore interventions that could reduce the risk for future outcome or ameliorate its effects in order to provide insights for improved care and management strategies. Method The study was conducted in Embase (1946-2020), Ovid Medline (1950-2020) and Pubmed databases (1960-2020) using the PICO framework. Primary studies (RCTs) on type 2 diabetes mellitus (T2DM) and inflammatory activities in diabetes-related angiopathies were included. Terms for the review were retrieved from the Cochrane library and from PROSPERO using its MeSH thesaurus qualifiers. Nine articles out of 454 total hits met the eligibility criteria. The quality assessment for the selected study was done using the Centre for Evidence-Based Medicine Critical Appraisal Sheet. Results Data analysis showed that elevated CRP, TNF-α and IL-6 were the most commonly found inflammatory indicator in diabetes-related angiopathies, while increased IL-10 and soluble RAGE was an indicator for better outcome. Use of drugs such as salsalate, pioglitazone, simvastatin and fenofibrate but not glimepiride or benfotiamine reported a significant decrease in inflammatory events. Regular exercise, consumption of dietary supplements such as ginger, hesperidin which have anti-inflammatory properties, and those containing prebiotic fibers (e.g. raspberries) revealed a consistent significant (p < 0.05) reduction in inflammatory activities. Conclusion Inflammatory activities are implicated in diabetes-related angiopathies; the intake of healthy dietary supplements, regular exercise and medications with anti-inflammatory properties could result in improved protective risk outcome for diabetes patients by suppressing inflammatory activities and elevating anti-inflammatory events.